2021
DOI: 10.1108/ecam-04-2021-0333
|View full text |Cite
|
Sign up to set email alerts
|

Can relational governance improve sustainability in public-private partnership infrastructure projects? An empirical study based on structural equation modeling

Abstract: PurposeAccording to relational contract theory, relational governance has potential to improve public-private partnership (PPP) infrastructure project sustainability. The main purpose of this research is to investigate the association between relational governance and the sustainability of PPP infrastructure projects. Further, this study examines the mediating effect of managerial innovation and the moderating role of public involvement.Design/methodology/approachResearch data were collected from 158 valid que… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 115 publications
1
13
0
Order By: Relevance
“…The results of the structural equation model show that both contractual and relational governance significantly improve the sustainable performance of PPP projects when the two governance mechanisms work together. This finding supports the views of Cheng et al [13] and Tian [12] respectively.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…The results of the structural equation model show that both contractual and relational governance significantly improve the sustainable performance of PPP projects when the two governance mechanisms work together. This finding supports the views of Cheng et al [13] and Tian [12] respectively.…”
Section: Discussionsupporting
confidence: 92%
“…Through communication, more comprehensive messages can be delivered, and information asymmetry between partners can be reduced, thus reducing transaction costs and coordination costs [3]. Studies have also shown that communication and trust have a mutually reinforcing effect and can effectively alleviate opportunism [12]. Thirdly, reciprocity is a code of ethics [34].…”
Section: Relational Governance and Sustainable Performance Of Ppp Pro...mentioning
confidence: 99%
See 1 more Smart Citation
“…VFM is used to evaluate whether PPP projects can create value [12]. The 3E principle including economy, efficiency, and effectiveness is widely adopted in government capital efficiency audits to evaluate whether a project achieved VFM [18]. Based on the 3E principles of VFM, various performance objectives of PPP projects are proposed to promote effective cooperation between the public and private sectors and achieve value creation.…”
Section: Value Creation Of Ppp Projectsmentioning
confidence: 99%
“…The PPP model is changing from high-speed to high-quality development. "Implementation Opinions on Promoting the Standardized Development of Government and Social Capital Cooperation" issued by China s Ministry of Finance in 2019 emphasizes that PPP projects should strictly perform VFM evaluation and promote PPP projects to create more value for society [18]. Therefore, achieving the basic performance management objectives in URT PPP projects can no longer meet the expectations of participants, but rather realize value-added through effective cooperation [5].…”
Section: Introductionmentioning
confidence: 99%